Choosing Among 3 Ankle-Foot Orthoses for a Patient With Stage II Posterior Tibial Tendon Dysfunction - NEVILLE, CHRISTOPHER (2009)
STUDY DESIGN: Case report. BACKGROUND: No head-to-head comparisons of different orthoses for patients with stage II posterior tibial tendon dysfunction (PTTD) have been performed to date. Additionally, the cost of orthoses varies considerably, thus choosing an effective orthosis that is affordable to the patient is largely a trial-and-error process. CASE DESCRIPTION: A 77-year-old woman was seen with complaints of abnormal foot posture (“my foot is out”), minimal medial foot and ankle pain, and a 3-year history of conservatively managed stage II PTTD. The patient was not able to complete 1 single-limb heel rise on the involved side, while she could complete 3 on the uninvolved side. Ankle strength testing revealed a mild to moderate loss of plantar flexor strength (20%–31% deficit on the involved side), combined with a 22% deficit in isometric ankle inversion and forefoot adduction strength. To assist this patient in managing her flatfoot posture and PTTD, 3 orthoses were considered: an off-the-shelf ankle-foot orthosis (AFO), a custom solid AFO, and a custom articulated AFO. The patient’s chief complaint was partly cosmetic (“my foot is out”). As decreasing flatfoot kinematics may unload the tibialis posterior muscle, thus prevent the progression of foot deformity, the primary goal of orthotic intervention was to improve flatfoot kinematics. Given the difficulties in clinical approaches to evaluating flatfoot kinematics, a quantitative gait analysis, using a multisegment foot model, was used. OUTCOMES: In the frontal plane, all 3 orthoses were associated with small changes toward hindfoot inversion. In the sagittal plane, between 2.7° and 6.1°, greater forefoot plantar flexion (raising the medial longitudinal arch) occurred. There were no differences among the orthoses on hindfoot inversion and forefoot plantar flexion. In the transverse plane, the off-the-shelf design was associated with forefoot abduction, the custom solid orthosis was associated with no change, and the custom articulated orthosis was associated with forefoot adduction. DISCUSSION: Based on gait analysis, the higher-cost custom articulated orthosis was chosen as optimal for the patient. This custom articulated orthosis was associated with the greatest change in flatfoot deformity, assessed using gait analysis. The patient felt it produced the greatest correction in foot deformity. Reducing flatfoot deformity while allowing ankle movement may limit progression of stage II PTTD.